1995
DOI: 10.1111/j.1600-0714.1995.tb01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ras p21 expression in oral premalignant lesions and squamous cell carcinomas in Taiwan

Abstract: Expression of ras p21 oncoproteins was examined in histological sections of oral squamous cell carcinoma (SCC), epithelial dysplasia, epithelial hyperkeratosis and normal oral mucosa using antibodies to ras p21 with an immunoperoxidase technique. Ras p21-positive staining was found in 47 of 51 (92.2%) cases of oral SCC, 4 of 4 (100%) cases of epithelial dysplasia, 7 of 7 (100%) cases of epithelial hyperkeratosis, and 1 of 6 (16.7%) cases of normal oral mucosa. The positive staining rate of ras p21 in oral SCC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Similarly, recent study has found that BQ ingredients may stimulate Src activation in oral cancer epithelial cells to promote cell migration and tumor invasion [39]. An elevated expression of Ras and mutation of Ras in oral premalignant lesions and OSCC of BQ chewers has been reported [14], [40]. This indicates that activation of Src and Ras is important in the BQ carcinogenesis.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, recent study has found that BQ ingredients may stimulate Src activation in oral cancer epithelial cells to promote cell migration and tumor invasion [39]. An elevated expression of Ras and mutation of Ras in oral premalignant lesions and OSCC of BQ chewers has been reported [14], [40]. This indicates that activation of Src and Ras is important in the BQ carcinogenesis.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies in our laboratory discovered that the expression of p53, PCNA and p21 ras was often higher in oral cancers and precancerous lesions from BQ chewers as compared to that of non-chewers [24][25][26][27]. Lee et al [28] showed that the average proportion of deleted mtDNA was significantly higher in non-tumor oral tissues from BQ chewers comparing to those of non-chewers.…”
Section: Discussionmentioning
confidence: 93%
“…Also, As skin lesions in Inner Mongolia were shown to be related to markers of oxidative DNA damage (Fujino et al 2005). However, no association was found between smoking and As-related skin cancer (Chen et al 2003) or cutaneous squamous cell carcinoma (Odenbro et al 2005), although overexpression of ras p21 oncoproteins has been suggested to play a role in the initiation and progression of oral squamous cell carcinoma in smokers (Kuo et al 1995). …”
Section: Discussionmentioning
confidence: 99%